Exploring the Therapeutic Potential of Grapeseed Phytoconstituent Through Molecular Docking Analysis for Multiple System Atrophy Treatment - Fatima Abdul Azeez (International Journal of Molecular Biotechnological Research, 2024)
Objective: Alpha-synuclein (α-Syn) aggregates are a common neurodegenerative disorder associated with Parkinson’s disease and multiple system atrophy (MSA). As a fruit that is extensively grown, grapes have several pharmacological advantages when it comes to reducing oxidative stress. Research has indicated that grape seed phytoconstituents have a major effect on α-Syn. The objective of this study is to inquire into the pharmacological characteristics and potential therapeutic applications of grape seed derivatives against the targeted protein, α-Syn. Methods: To assess their binding affinity with α-Syn, thirty distinct grape seed components and their phytoconstituents were chosen for this investigation. The PyRx virtual tool was employed for molecular docking processes, utilizing computational analysis based on the molecular structures of both phytocompounds and α-Syn. The protein structure was verified using a collection of tools, such as the PDBsum generator and BIOVIA Discovery studio program. Furthermore, ADMET filters were used to evaluate the ligands pharmacologically. Result: The molecular docking studies indicated that thiamine, the ligand, had a low binding affinity for the protein α-Syn, which was the target. Conclusion: As thiamine has been shown to be a therapeutic agent against α-Syn in Parkinson’s disease research, it may be a good choice for MSA and can be utilized to lessen its effects. To validate these results, in vitro studies are still necessary
Keywords: ADMET analysis; Multiple system atrophy; Ramachandran plot; alpha-synuclein; grapeseed; molecular docking; phytoconstituents; thiamine